Lasers and Nuclei Applications of Ultrahigh Intensity Lasers in Nuclear Science - Schwoerer, Heinrich; Magill, Joseph; Beleites, Burgard (Lecture Notes in Physics,, 2006)
Lasers and Nuclei describes the generation of high-energy-particle radiation with high-intensity lasers and its application to nuclear science. A basic introduction to laser--matter interaction at high fields is complemented by detailed presentations of state of the art laser particle acceleration and elementary laser nuclear experiments. The text also discusses future applications of lasers in nuclear science, for example in nuclear astrophysics, isotope generation, nuclear fuel physics and proton and neutron imaging.